Surgical outcome and prognostic factors in spinal cord ependymoma: a single-center, long-term follow-up study - Oliver Gembruch (SAGE Publishing, 2021)
Objective: Spinal cord ependymomas account for 3–6% of all central nervous system tumors and around 60% of all intramedullary tumors. The aim of this study was to analyze the neurological outcome after surgery and to determine prognostic factors for functional outcome. Patients and Methods: Patients treated surgically due to a spinal cord ependymoma between 1990 and 2018 were retrospectively included. Demographics, neurological symptoms, radiological parameters, histopathology, and neurological outcome (using McCormick Score [MCS]) were analyzed. Possible prognostic factors for neurological outcome were evaluated. Results: In total, 148 patients were included (76 males, 51.4%). The mean age was 46.7 ± 15.3 years. The median follow-up period was 6.8 ± 5.4 years. The prevalence was mostly in the lumbar spine (45.9%), followed by the thoracic spine (28.4%) and cervical spine (25.7%). Gross-total resection was achieved in 129 patients (87.2%). The recurrence rate was 8.1% and depended on the extent of tumor resection ( p  = 0.001). Postoperative temporary neurological deterioration was observed in 63.2% of patients with ependymomas of the cervical spine, 50.0% of patients with ependymomas of the thoracic spine, and 7.4% of patients with ependymomas of the lumbosacral region. MCS 1–2 was detected in nearly two-thirds of patients with cervical and thoracic spinal cord ependymoma 36 months after surgery. Neurological recovery was superior in thoracic spine ependymomas compared with cervical spine ependymomas. Poor preoperative functional condition (MCS >2), cervical and thoracic spine location, and tumor extension >2 vertebrae were independent predictors of poor neurological outcome. Conclusion: Neurological deterioration was seen in the majority of cervical and thoracic spine ependymomas. Postoperative improvement was less in thoracic cervical spine ependymomas compared with thoracic spine ependymomas. Poor preoperative status and especially tumor extension >2 vertebrae are predictors of poor neurological outcome (MCS >2).